Family Health Support Center on the professional’s perspective: assumptions and developed experiences (Research, Society and Development, 2020)
The study aimed to investigate the professional’s knowledge on the legal boundaries that underlie the NASF, and the weaknesses and strengths developed in the Basic Care (AB). The research was conducted with 29 NASF’s professionals in a city on the coast of Paraiba, Brazil. The interviews followed a half-structured script and its transcriptions were submitted to a Content Analysis. The interviewees showed a deficit regarding their knowledge and appropriation of knowledge about the documents under discussion and they acknowledged the existing obstacles in their technique, emphasizing as weaknesses the work in the Health Care Networks (RAS), as well as the high demand of specialized services. Despite de difficulties, they pointed out the importance of a multidisciplinary team and the inter-branch actions, extremely important to extended assistance, AB’s care and consolidation in the SUS.